Imported models : a tradition of english-language teaching in Portugal - Torre, Manuel Gomes da (1995)
In this paper I try to demonstrate how the importance of the English language outside Britain was recognised by early Portuguese grammarians and how the latter were attentive, especially during the eighteenth and nineteenth centuries, to foreign models and transferred them to their books.